2003
DOI: 10.1093/alcalc/agg019
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Suicide Probability in Alcoholic in-Patients

Abstract: It was found that self-esteem, depression and trait anxiety predict suicide probability. Suicide probability was higher within the sub-sample with a history of a suicidal act in comparison to those without such a history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Of all depressive symptoms, hopelessness has been identified as a particularly strong predictor of suicidal behavior; it is discussed later in this article. Low self-esteem is another symptom that is frequently comorbid with substance dependence and has been shown to be a significant predictor of suicide probability (Demirbas, Celik, Ilhan, & Dogan, 2003). Risk is especially high early in the course of bipolar disorders.…”
Section: Iii: Symptomatic Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all depressive symptoms, hopelessness has been identified as a particularly strong predictor of suicidal behavior; it is discussed later in this article. Low self-esteem is another symptom that is frequently comorbid with substance dependence and has been shown to be a significant predictor of suicide probability (Demirbas, Celik, Ilhan, & Dogan, 2003). Risk is especially high early in the course of bipolar disorders.…”
Section: Iii: Symptomatic Presentationmentioning
confidence: 99%
“…Patients who report anhedonia and insomnia combined with severe anxiety symptoms, alcohol abuse, or emotional turmoil associated with continuously cycling moods are at greatest short-term risk for suicide (Kleespies & Dettmer, 2000). The nature and duration of anxiety symptoms are important variables for consideration, as trait anxiety has a stronger relationship with suicide probability than state anxiety (Demirbas, Celik, Ilhan, & Dogan, 2003;Goldston et al, 1999).…”
Section: Iii: Symptomatic Presentationmentioning
confidence: 99%
“…Alcoholdependent individuals with a history of suicide attempts were found to have a significantly more severe course of alcohol dependence and a higher prevalence of both independent and substance-induced psychiatric disorders and other substance dependence (1). It was found that selfesteem, depression and trait anxiety predict suicide probability in Turkish alcoholics (6). Significantly more of the drug-dependent patients who had attempted suicide had a lifetime history of major depression (2).…”
mentioning
confidence: 99%
“…Since suicide probability is higher in the subgroup of substance dependents with SAH (6), this group needs special attention. In a cohort of suicide attempters, male gender and substance use disorders were found as significant risk factors for both later suicide and other causes of death (10).…”
mentioning
confidence: 99%
“…Suicidal behavior is complex and heterogeneous (16). Among other risk factors, history of suicide attempt (HSA) appears to be the strongest known predictor of completed suicide in alcohol dependents (17). Suicidal behavior is very common among alcohol dependent individuals (18,19).…”
Section: Introductionmentioning
confidence: 99%